2016
DOI: 10.1002/jor.23281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subchondral bone histopathology of facet joint osteoarthritis in lumbar spinal stenosis

Abstract: Facet joint osteoarthritis may be a cause of low back pain in degenerative spine diseases including lumbar spinal stenosis. Subchondral bone is regarded as a potential therapeutic target for osteoarthritis treatment. The goal of this study was to characterize subchondral bone histopathology in osteoarthritic facet joints from lumbar spinal stenosis patients. Fifteen patients with degenerative spinal stenosis scheduled for transforaminal lumbar interbody fusion surgery were recruited for this study. Osteoarthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…However, BMSC‐exosomes could partially reverse the degenerated changes. Impairments of subchondral appear in parallel to the cartilage degeneration, which might accelerate cartilage damage as previously reported . While BMSCs‐exosomes simultaneously improve the reconstruction of cartilage and subchondral bone, supporting the notion that the cross‐talk between them maintains the physiological environment for articular in a synergistic approach.…”
Section: Discussionsupporting
confidence: 76%
“…However, BMSC‐exosomes could partially reverse the degenerated changes. Impairments of subchondral appear in parallel to the cartilage degeneration, which might accelerate cartilage damage as previously reported . While BMSCs‐exosomes simultaneously improve the reconstruction of cartilage and subchondral bone, supporting the notion that the cross‐talk between them maintains the physiological environment for articular in a synergistic approach.…”
Section: Discussionsupporting
confidence: 76%
“… 9 The main pathologic changes include osteoproliferation of the lamina and facet joints, protrusion of the vertebral discs, and hypertrophy of the ligamentum flavum, with the last being the main cause of the spinal stenosis. 10 12 Repeated mechanical stretching due to instability of the degenerative lumbar spine is reportedly the main reason for injury to the ligamentum flavum, which leads to regional scar formation and hypertrophy of the ligament. 4 Suppression of the cauda equina by the ligamentum flavum is normally the cause of symptoms in patients with hypertrophy of the ligamentum flavum.…”
Section: Discussionmentioning
confidence: 99%
“…Both nociceptive nerve fibers and neuromodulators, such as substance P and nerve growth factor, have been identified in capsular tissues of degenerative facet joints. It has been shown that enhanced remodeling of subchondral bone and marrow tissues is a predominant feature in the trabecular compartment in FJOA [ 14 , 15 , 16 ]. Elevated active bone-forming osteoblasts accompanied by excessive collagen fiber deposition were indicative of a shift towards bone formation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%